2018
DOI: 10.1021/acsanm.8b00918
|View full text |Cite
|
Sign up to set email alerts
|

Sub-1 nm Equivalent Oxide Thickness Al-HfO2 Trapping Layer with Excellent Thermal Stability and Retention for Nonvolatile Memory

Abstract: Memory stacks for charge trapping cells have been produced exploiting Al-doped HfO2, Al2O3, and SiO2 made by atomic layer deposition. The fabricated stacks show superior stability and electrical characteristics, allowing for the engineering of sub-1 nm equivalent oxide thickness Al doped HfO2 trapping layer with excellent retention characteristics, also at high temperature. The low Al doping content (4.5%) used in this work leads to the HfO2 crystallization, upon thermal annealing, in the cubic/tetragonal phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 43 publications
0
5
0
1
Order By: Relevance
“…Oxides of valve metals have shown remarkable performances as memristive elements. Studies on Hf- and Ta-based memristors reported excellent electrical and memory properties, such as multilevel switching, high endurance, and data retention. , The deposition of oxide layers is commonly done by atomic layer deposition , or sputtering . Alternatively, the electrochemical anodization process is a faster, less complex, and inexpensive method, with precise composition and oxide thickness control through electrochemical parameters. , …”
mentioning
confidence: 99%
“…Oxides of valve metals have shown remarkable performances as memristive elements. Studies on Hf- and Ta-based memristors reported excellent electrical and memory properties, such as multilevel switching, high endurance, and data retention. , The deposition of oxide layers is commonly done by atomic layer deposition , or sputtering . Alternatively, the electrochemical anodization process is a faster, less complex, and inexpensive method, with precise composition and oxide thickness control through electrochemical parameters. , …”
mentioning
confidence: 99%
“…[26][27][28][29][30][31] Of these, HfO x is CMOS compatible and offers many benefits, including a high dielectric constant (∼25) and a wide bandgap (∼6 eV). 32,33 Moreover, HfO x -based RRAM relies on the formation and rupture of conductive filaments, which are produced by the migration of oxygen vacancies within the switching layer. 34,35 Accordingly, it is important to determine the factors that improve reliability (especially in vertically stacked structures), because it is challenging within RRAM to handle the intrinsically and stochastically generated filaments.…”
Section: Introductionmentioning
confidence: 99%
“…Большинство мемристивных устройств на данный момент изготавливается с использованием неорганических материалов (TiO 2 , ZnO, HfO 2 , WO 3 , SiO 2 и др.) [6][7][8][9]. Наряду с неорганическими мемристорами все больший интерес начинают вызывать мемристоры на основе органических материалов, так как они не уступают неорганическим по основным параметрам [10], но при этом обладают рядом преимуществ, например относительно малой стоимостью, простотой изготовления, гибкостью и биосовместимостью [11,12].…”
Section: поступило в редакцию 9 октября 2019 г в окончательной редакunclassified